2018
DOI: 10.5704/moj.1803.007
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Primary Cemented Bipolar Hemiarthroplasty compared with Dynamic Hip Screw in Elderly Patients with Unstable Intertrochanteric Fracture

Abstract: Introduction: Although the treatment of choice for unstable intertrochanteric fractures in elderly patients has been internal fixation for a long time, several studies have shown mechanical and technical failures. Primary cemented bipolar (PCB) hemiarthroplasty has been proposed as an alternative with some advantages concerning earlier mobilization and minimal postoperative complications.Materials and Methods: This is a prospective cohort hospital-based study conducted at three tertiary hospitals over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In addition, the time required to reduce the incidence of fracture is an important variable that cannot be standardized. The greater postoperative reduction in hemoglobin and albumin levels is also similar to the findings of a large multicenter study by Ekinci et al that compared arthroplasty and internal fixation [ 23 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, the time required to reduce the incidence of fracture is an important variable that cannot be standardized. The greater postoperative reduction in hemoglobin and albumin levels is also similar to the findings of a large multicenter study by Ekinci et al that compared arthroplasty and internal fixation [ 23 ].…”
Section: Discussionsupporting
confidence: 85%
“…We used the claw hook to adduct the greater trochanter to facilitate cutting off the lateral rotator muscles, thereby opening the joint capsule and subsequent osteotomy of the femoral neck. Third, as Gashi et al reported in 2018, titanium cable or cementum can be used for greater trochanter fixation and intertrochanteric reinforcement [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing age and osteoporosis present treatment issues due to compromised biomechanical structural strength of the femur. Additionally, internal fixation loosening, cutting, nonunion, coxa vara and other problems may occur following treatment [79].…”
Section: Introductionmentioning
confidence: 99%